The solution of twocomponent boundary layer with the heat transfer at the border. (Journal of Mathematics Mechanics and Computer Science, 2012)
In this paper, we consider a system of equations of two-phase warm boundary layer near the surface rupture of the plate at an arbitraryrate of injection. The boundary condition relative to temperature determines the process of convective heat transfer between the surface plate and the environment (injected luid) The method of successive approximationsof the problem reduces to solving an integro-differential equations with relative to temperature. It was based on the zero order approximation formulas are constructed first approximation for the temperature field.